2016
DOI: 10.1002/ps.4218
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate residues in rural groundwater, Nottawasaga River Watershed, Ontario, Canada

Abstract: The glyphosate/AMPA detections in riparian seeps demonstrated that these compounds are persistent enough to allow groundwater to store and transmit glyphosate residues to surface waters. Detections in the wetlands support earlier evidence that atmospheric transport and deposition may lead to glyphosate contamination of environments not intended as targets of applications. This interpretation is further supported by detections of both glyphosate and AMPA in precipitation samples collected in the same watershed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…The Nottawasaga River has its headwaters in the Oak Ridges Moraine and discharges to Georgian Bay at Wasaga Beach. Land use in the Nottawasaga River Watershed (3147 km 2 ) consists largely of agriculture (56%), with potatoes ( Solanum tuberosum L.) and sod being major crops in the southern portion of the watershed (Van Stempvoort et al, 2016) where groundwater was collected for this study. The basin has a temperate climate and receives ∼790 mm of precipitation annually, with ∼20% coming in the form of snow (Environment and Climate Change Canada, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The Nottawasaga River has its headwaters in the Oak Ridges Moraine and discharges to Georgian Bay at Wasaga Beach. Land use in the Nottawasaga River Watershed (3147 km 2 ) consists largely of agriculture (56%), with potatoes ( Solanum tuberosum L.) and sod being major crops in the southern portion of the watershed (Van Stempvoort et al, 2016) where groundwater was collected for this study. The basin has a temperate climate and receives ∼790 mm of precipitation annually, with ∼20% coming in the form of snow (Environment and Climate Change Canada, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Glyphosate has also been indicated as a significant water pollutant from intensive agriculture in Mexico (Ruiz-Toledo et al, 2014). The concentrations of glyphosate in surface waters in the EU appears to be lower, but consistently occurring e.g., Germany (Skark et al, 1998), the Mediterranean (Barceló and Hennion, 1997), the Northern region Lode, 2001, 2002;Kjaer et al, 2005), in France (Botta et al, 2009;Van Stempvoort et al, 2016;Clausing et al, 2018) and elsewhere, and its dissipation has been found to be slowed down in formulation and in the presence of algal biofilms (Klátyik et al, 2017b). Thus, glyphosate residues have been deemed to be worldwide the most common pesticide contaminant in freshwater ecosystems, AMPA being the most frequent, glyphosate being the third most frequent contaminant in France (Villeneuve et al, 2011).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…Glyphosate and AMPA transport can occur with favorable hydrological factors, where they are stable in soils, air or water. Van Stempvoort et al (2016) showed that glyphosate and AMPA are persistent enough to reach shallow groundwater, be stored in it and then M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 13 transferred to surface water. Leaching of glyphosate and AMPA through soil seems to be a slow, minor phenomenon, according to Bergström et al (2011).…”
Section: Transport Across Soilmentioning
confidence: 99%